The risk assessment of threats from biological objects in environmental safety - Kryvomaz, T.; Voloshkina, O. (KNUCA, 2014)
Necessity to present results of scientific research in an accessible form for proper interpretation by public and environmental safety experts has been shown. Myxomycetes ecology and metabolism to verify their safety for human health has been evaluated as an example. Bayesian methods for probability analysis is proposed to be used for risk assessment. The "Environmental safety passports of species" are recommended for evaluation of impact of each species on the environment, humans and other living organisms.
Оценка риска угроз со стороны биообъектов в сфере экологической безопасности
Keywords: environmental safet; risk assessment; myxomycetes; ecological passpor; экологическая безопасность; оценка рисков; миксомицеты; экологический паспорт